Outcome Monitoring After Cardiac Surgery (OMACS): a single-centre prospective cohort study of cardiac surgery patients. Issue 12 (19th December 2022) - Walker-Smith, Terrie; Joyce, Katherine; Maishman, Rachel; Smartt, Helena; Hopkins, Emma; Brierley, Rachel; Reeves, Barnaby C; Rogers, Chris A; Angelini, Gianni D; Culliford, Lucy
Abstract : Introduction: More than 30 000 cardiac surgery procedures are performed in the UK each year, however, postoperative complications and long-term failure of interventions are common, leading to repeated surgeries. This represents a significant burden on the patient and health service. Routinely, patients are discharged to their general practitioner 6 weeks postoperatively and research studies typically only report short-term outcomes up to 1 year after surgery, together this makes long-term outcomes of cardiac surgery difficult to monitor. Further, traditional research methods have yet to advance understanding of what causes early complications and why surgical interventions fail. Methods and analysis: This prospective cohort study will characterise participants undergoing cardiac surgery at baseline, describe short-term, medium-term and long-term health outcomes postoperatively and collect tissue samples. All eligible adult patients undergoing cardiac surgery at the Bristol Heart Institute, UK will be approached for consent. Recruitment is expected to continue for up to 10 years resulting in the largest cohort of cardiac patients reported to date. Blood, urine and waste tissue samples will be collected during admission. Samples, along with anonymised data, will be used to investigate outcomes and inform predictive models of complications associated with cardiac surgery. Data about the surgical admission will be obtained from hospital databases and medical notes. Participants may be monitored up to 5 years postoperatively using data obtained from NHS digital. Participants will complete health questionnaires 3 months and 12 months postoperatively. The analysis of data and tissue samples to address specific research questions will require separate research protocols and ethical approval. Ethics and dissemination: This study was approved by the East Midlands Nottingham 2 Research Ethics Committee. Findings will be disseminated through peer-reviewed publications and presentation at national and international meetings. Participants will be informed of results in annual newsletters. Trial registration number: ISRCTN90204321 .